Awareness of glaucoma, and health beliefs of patients suffering primary acute angle closure. Issue 4 (1st April 2003) - Saw, S-M; Gazzard, G; Friedman, D; Foster, P J; Devereux, J G; Wong, M L; Seah, S
Abstract : Aim: To evaluate the factors associated with lack of awareness of glaucoma and late presentation to the doctor in Singapore Chinese patients with acute angle closure (AAC) Methods: A prospective, hospital based case series of 105 patients aged 35 years and above who presented with a first attack of AAC in a tertiary hospital in Singapore was conducted. A research assistant interviewed all patients face to face in clinic and recorded demographic factors, awareness of glaucoma, and subjective barriers to seeing a doctor. The time from onset of symptoms to presentation at the clinic was noted. Results: Overall, 22.9% of patients had heard of glaucoma. The multivariate adjusted odds ratio (OR) of unawareness of glaucoma in older people (> 60 years) was 1.5 (95% confidence interval (CI) 0.5 to 4.6), 3.2 (95% CI 1.1 to 9.2) for adults who were not working, and 13.8 (95% CI 1.3 to 146.7) for patients who had less than a pre-university education. A significant proportion (31.7%) of patients presented to the doctor 24 hours or more after symptoms occurred. In a multiple logistic regression model, the adjusted OR of late presentation was 8.5 (95% CI 1.04 to 69.5) if there was no car access, 5.0 (95% CI 1.0 to 24.6) if the patients spoke Chinese, and 3.3 (95% CI 0.9 to 11.9) if there was nobody to accompany to hospital. Conclusion: Glaucoma awareness among patients suffering AAC was not high. Lack of awareness was associated with increasing age, lack of formal education, and unemployment. A significant proportion of patients seek medical attention late. Risk factors for late presentation include lack of car access, nobody to accompany the patient, and speaking the Chinese language primarily. Health education programmes may help increase the knowledge and awareness of glaucoma.